(untitled) - Miller, Judy L. (New York, 2001)
The reason to write series offers students strategies and practice in writing for academic success. Students are carefully guided through the stages of writing, from generating ideas.
Keywords: English language,English language,Academic writing,Ngôn ngữ Anh,Ngôn ngữ Anh; Rhetoric,Giáo trình dành cho người nước ngoài,Tu từ học